Protocol for the development and validation of a clinical measurement tool for fear of disease progression and recurrence in cardiac patients - Sarah T. Clarke; Michael Le Grande; Barbara M. Murphy; Robert Hester; Alun C. Jackson (Chronic Diseases and Translational Medicine, 2024)
Abstract Introduction One in two cardiac patients fear having another heart event or their heart condition getting worse. Research in other chronic illnesses demonstrates that screening for fear of progression and recurrence is vital for adequately addressing such concerns in clinical care. The current project aims to develop and validate a measure for fear of progression and recurrence in cardiac patients. Methods The Fear of Cardiac Recurrence and Progression Scale (FCRP) will be developed through a multistep process. An initial item pool will be generated through a review of the literature and existing measures and consultation with and feedback from key informants. The item pool will be tested in a sample of over 250 adults who have ever had an acute coronary event, undergone cardiac surgery, or a chronic cardiac condition. Exploratory factor analysis will be used to identify the underlying factors, and Rasch analysis will be used to reduce the number of items. A short form version of the FCRP will be developed for use as a brief screening tool, informed by clinical relevance and Rasch psychometric indices. Discussion While many cardiac patients experience fears related to the progression or recurrence of their illness, there remains the need for a validated tool with which these concerns can be identified and measured. It is expected that the design and validation of the FCRP will aid identification of cardiac patients suffering from clinically significant levels of fear of progression and recurrence and facilitate the design of tailored psychological interventions to target these fears.